Analysis of Factors Affecting Vannamei Shrimp Production During the Pandemic (Covid-19) in Mawasangka District Central Buton Regency - Yuliana, Yuyun; Limi, Muhammad Aswar; Slamet, Agustono (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
This research was conducted in Mawasangka District, Central Buton Regency. This research determines how much vannamei shrimp production is and analyzes what factors influence vannamei shrimp production. The population in this study was 45 vannamei shrimp farmers. Sampling in this study was using the census method, where researchers took the entire population of vannamei shrimp pond farmers in Mawasangka District. The analysis was used to determine the number of products produced by vannamei shrimp farmers using quantitative analysis with rumours of productivity and production function of Cobb Douglass to examine the factors that influence production. The results showed that the total production of vannamei shrimp was 14,319 tons, with an average output of 318 kg / 2HA. Factors that significantly affect the production island area (X1 ), Shrimp (X2 ), and Feed (X4 ) where the results uj i in getting the Sig and n use-values the coefficient of determination is 0 .563, which means production factors size fries, lime. Feed collectively together has an influence on the production amounted to 56.7%.